Combined satellite and radar retrievals of drop concentration and CCN at convective cloud base. Issue 9 (7th May 2014) - Rosenfeld, Daniel; Fischman, Baruch; Zheng, Youtong; Goren, Tom; Giguzin, David
Abstract The number of activated cloud condensation nuclei (CCN) into cloud drops at the base of convective clouds (Na) is retrieved based on the high‐resolution (375 m) satellite retrievals of vertical profiles of convective cloud drop effective radius (re). The maximum cloud base supersaturation (S) is calculated when Na is combined with radar‐measured updraft and yields CCN(S), which was validated well against ground‐based CCN measurements during the conditions of well‐mixed boundary layer over the U.S. Department of Energy's Atmospheric System Research Southern Great Plains site. Satellite retrieving Na is a new capability, which is one essential component of simultaneous measurements of cloud microstructure and CCN from space by using clouds as natural CCN chambers. This has to be complemented by a methodology for satellite estimates of cloud base updraft, which is yet to be developed and demonstrated. In the mean time, the retrieved Na can be used for the assimilation of the combined CCN and updraft effects on clouds in models.